Using Caloric Efficiency to Estimate the Energy Value of Soybean Meal Relative to Corn and Its Effects on Growth Performance of Nursery Pigs - H. S. Cemin; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2019)
An experiment was conducted to estimate the energy value of soybean meal (SBM) relative to corn and determine the effects of increasing amounts of SBM in nursery pig diets. A total of 2,233 pigs (PIC 337 × 1050, Hendersonville, TN), initially 24.2 lb body weight (BW), were placed in 92 pens with 20 to 27 mixed gender pigs per pen. After weaning, pigs were fed common diets for 21 d and then assigned to treatments in a randomized complete block design with BW as the blocking factor. Treatment diets consisted of 21, 27, 33, or 39% SBM, obtained by changing the amount of feed-grade amino acids (AA) and corn, and were fed for 21 d. Soybean meal NE value used in diet formulation was 947 kcal/lb. There were 23 replicates per treatment. Pigs were weighed and feed disappearance measured to calculate average daily gain (ADG), average daily feed intake (ADFI), feed efficiency (F/G), and caloric efficiency (CE). Data were analyzed using the GLIMMIX procedure of SAS with block as a random effect and treatment as a fixed effect. Single degree-of-freedom contrasts were constructed to test the linear and quadratic effects of increasing SBM. There was a tendency (P= 0.090) for a quadratic response for ADG, with an improvement observed up to 33% SBM. There was a tendency (linear,P= 0.092) for a decrease in ADFI as dietary SBM increased. Pigs fed diets with increasing SBM had a tendency (quadratic,P= 0.066) for an improvement in F/G up to 33% SBM then returned to control values when 39% SBM was fed. There was an improvement (linear,P= 0.001; quadratic,P= 0.065) in CE with increasing SBM. Using CE as a means to estimate the energy content of SBM relative to corn, a value of 105.4% of corn energy or 1,277 kcal/lb NE was determined using all 4 data points. When removing the CE value of the 39% SBM treatment due to the quadratic tendency and just using the linear portion of the CE response, SBM was estimated to have 121.1% of corn energy or 1,468 kcal/lb NE. In conclusion, the results of the current study suggest that feeding SBM up to 33% improves ADG, F/G, and CE. The energy value of SBM is estimated between 105 and 121% of corn, much greater than the current suggested value of 78% of corn. This has important ramifications as it increases the value of SBM in diet formulation.
Keywords: caloric efficiency energy; soybean meal; swine